ANALYSIS OF POST-OPERATIVE PAIN IN ROOT CANAL THERAPY USING CALCIUM HYDROXIDE (CA(OH)₂)-BASED SEALER - Sarah Shami; Zobia Batool; Muhammad Moazzam; Nayab Amin; Kashif Haroon; Maria Noor (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Post-operative pain is a common concern in root canal therapy (RCT), affecting patient comfort and treatment outcomes. Calcium hydroxide (Ca(OH)₂)-based sealers are hypothesized to provide better pain relief and healing due to their anti-inflammatory and antimicrobial properties.Objective: To evaluate the impact of Ca(OH)₂-based sealers on post-operative pain, analgesic consumption, and healing outcomes compared to non-Ca(OH)₂-based sealers in RCT.Study Design & Setting: This experimental study was conducted at Sharif Medical & Dental College, Lahore over six months from Jan 2023 to June 2023.Methodology: A total of 150 patients were randomly allocated into two groups: an experimental group using Ca(OH)₂-based sealers and a control group using non-Ca(OH)₂-based sealers. Standardized RCT procedures were performed, and post-operative pain was assessed using a visual analog scale (VAS) at 6, 24, 48, and 72 hours. Analgesic consumption and healing outcomes were also recorded. Statistical analysis was performed using SPSS version 25.0, with p < 0.05 considered significant.Results: The experimental group demonstrated significantly lower pain scores at all-time points (p < 0.001). Analgesic consumption was reduced in the experimental group, with 24% requiring pain relief compared to 51% in the control group (p < 0.001). Complete healing was observed in 90.7% of the experimental group compared to 74.7% of the control group (p = 0.01).Conclusion: Ca(OH)₂-based sealers significantly reduce post-operative pain, lower analgesic requirements, and enhance healing outcomes, making them an effective choice for improving RCT success.